Planning without Prices - Heal, G. M. (Review of Economic Studies, 1969)
Journal Article Planning without Prices Get access G. M. Heal G. M. Heal Christ's College, Cambridge Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 36, Issue 3, July 1969, Pages 347–362, https://doi.org/10.2307/2296432 Published: 01 July 1969 Article history Received: 15 September 1968 Received: 15 February 1969 Published: 01 July 1969